Organo-chlorine residues in tissues of marine fauna along the coast of Kenya Mombasa Island - Bor, S.K.; Simbauni, J.A.; Oyugi, Mildred P.; Njue, Wilson N.; Chhabra, S.C. (My University, 2007)
Soft tissues of species of marine fauna; crabs (Crust acea ), oysters ( Pelecypoda, Bivalvia), sea stars ( Asterroidea ), sea urchin (Echinoidea) and bony fishes (Osteichtyes) sampled along the Kenya - Mombasa coastal region were analyzed to determine the levels of organochlorine pesticides (OCPs). Analysis was done using gas chromatography with an electron capture detector. This study showed that marine fauna accumulated some OCPs in their tissues, 1,2,3,4,5,6 - hexachlorocyclohexane (BHC) being the most common of the OCPs. These findings highlight evidence of pollution of marine fauna at the Kenyan coastal sites. It is necessary to have thorough waste management programs as a strategy to minimize marine pollution